ANALISIS PENGGUNAAN MAKNA DENOTATIF DAN MAKNA KONOTATIF PADA SYAIR IMAM SYAFI - Sinta Salsabila; Dini Sirma Budi (LPPM Universitas KH. A. Wahab Hasbullah, 2020)
This study aims to describe the denitative and connotative meanings of the Shafi’i priest poems. This type of reseaech is qualitive reseaech. The object of this research is the poetry weirren by Imam Shafi’i. The technique of collecting data in this study uses library techniques,and note taking. Data analysis for this study used the matching method. The results of this study are the first, in many poems weitten by Shafi Imam there are words that contain denotative meanings. Denotative meaning that is often used for everyday and easy to understand. Second, in the poem written by Shafi’i the priest also finds words that contain connotative meaning. The connotative meaning is divided into several, namely 1) high connotation, because of the words that contain high taste value; 2) friendly connotation, worth saying or disclosed to the speaker, 3) dangerous connotation, words that are often forbidden to be said in certain situations, 4) inappropriate connotations, words that should not be spoken and have a value of inappropriate taste; 5) connotations are not pleasant, words that are not pleasant to hear by the ear; 6) rough connotations, words that have a value of rough taste to be said, 7) hard connotation like words that have hyperbole meaning; 8) connotation that goes down, words that have meaning down from previous meanings; 9) connotation that go up, words that have meaning up from the previous meaning.